Implementing change in health systems : market reforms in the United Kingdom, Sweden, and the Netherlands - Harrison, Michael I. (Sage, 2004)
This comprehensive and comparative study of health service change focuses on the influence of health professionals on the process and shape of change. The book examines the development and implementation of national health system reorganizations in the UK, Sweden and the Netherlands. Separate chapters examine the development, implementation and outcomes of reform. The author′s research highlights a crucial link in the chain of implementation: the occupational and organizational consequences of reform for physicians and other health professionals and the way physicians influence programme implementation.